FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN STUNTING PADA BALITA USIA 24-59 BULAN DI DESA MALINAU HILIR KABUPATEN MALINAU - Gita Ekawati, (2021)
Stunting is a condition of delayed growth that is severe due to malnutrition in the long term. The causes of stunting are multifactorial and are not only influenced by inadequate nutrition during pregnancy and toddlers, one of the factors causing stunting is bad parenting from mother. The purpose of the study was to analyze the relation between feeding, hygiene, use of health facilities and psychosocial stimulation with toddler stunting. This study used a cross sectional design. The technique used in determining the sample is a purposive sampling and the results obtained 109 respondents. The study used mothers who had toddlers aged 24-59 months in Malinau Hilir Village, Malinau Regency. The instrument used is primary data by measuring the toddler's height using microtoise and questionnaires. Analysis of the data used is bivariate statistical test with Chi-Square Test. This study has the result that there is a relation between feeding (p = 0.002), hygiene (p = 0.001), use of health facilities (p = 0.000) and psychosocial stimulation (p = 0.004) with the stunting in toddlers aged 24 -59 months in Malinau Hilir Village, Malinau Regency. The conclusion of the study is that the factors related to the stunting in toddlers include feeding, hygiene, use of health facilities and psychosocial stimulation.